Training of Learning Model of Listening Team Type for Elementary School Teachers of Tanjung Mutiara, Agam Regency - Reinita, Reinita; Hidayat, Muhamad Taufik (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
The purpose of this community services to improve the knowledge and skills of elementary school teachers in Tanjung Mutiara, Agam, West Sumatera in applying Civics learning with Listening Team cooperative learning. This program was carried out in the form of training of two meetings. Presentation materials include an explanation of the learning model concept, examples of implementation in learning, making a lesson plan, simulation and assessment techniques. The methods used in this training were lecturing, question and answer, assignment, discussion, and simulation. This program can improve the skills of elementary school teachers in Tanjung Mutiara in designing and implementing Civics learning that is more attractive and stimulates the activity of elementary students. The program also enhances participants' motivation to improve their insights and knowledge related to cooperative learning models in general and to encourage participants to improve their professionalism in the implementation of learning, especially Civics learning.